MANAJEMEN PENGETAHUAN DAN KEMAMPUAN LINTAS BUDAYA SERTA PENGARUHNYA TERHADAP ADAPTABILITAS ORGANISASI - Pudjo - Sugito; Sumartono Sumartono (Faculty of Economics and Business Udayana University, 2018)
The aim of this research is to analyze the effect of knowledge management and cross cultural competence to the organizational adaptability. The research population are small and medium industries in Malang, amounting to 279 103 units (the Department of Cooperatives and SMEs, 2015). Data collection techniques used is proportional random sampling that is a unit sample selected based on certain considerations in order to obtain samples with specific characteristics. The number of respondents in this research determined the 200 respondents who are performing well, as a minimum requirement that is needed in data analysis techniques Structural Equation Model (SEM). Gradually, it will use two kinds of analysis techniques (1) factor analysis, is used to confirm the factors most dominant variable in one group and (2) regression weight in SEM, used for confirmatory examine how much the relationship between variables. Based on the results of data analysis revealed that knowledge management and cross cultural competency significantly effect to the organizational adaptability.